Insights Into the Molecular Mechanisms of Late Flowering in Prunus sibirica by Whole-Genome and Transcriptome Analyses - Xu, Wanyu; Bao, Wenquan; Liu, Huimin; Chen, Chen; Bai, Haikun; Huang, Mengzhen; Zhu, Gaopu; Zhao, Han; Gou, Ningning; Chen, Yixiao; Wang, Lin; Wuyun, Ta-na (Frontiers in Plant Science, 2022)
Freezing during the flowering of Prunus sibirica is detrimental to fruit production. Late flowering (LF) type, which delays 7-15 days compared with the normal flowering (NF) type, avoids damages at low temperature, but the molecular mechanism of the late flowering remains unclear. Therefore, this study was conducted to comprehensively characterize floral bud differentiation. A histological analysis showed that initial floral bud differentiation was delayed in the LF type compared to NF type. Genome-wide associated studies (GWAS) showed that a candidate gene (PaF106G0600023738.01) was significantly associated with late flowering. It was identified as trehalose-6-phosphate phosphatase (PsTPPF) being involved in Trehalose-6-phosphate (Tre6P) signaling pathway, that acts on floral transition. A whole-transcriptome RNA sequencing analysis was conducted, and a total of 6110 differential expression (DE) mRNAs, 1351 DE lncRNAs, and 148 DE miRNAs were identified. In addition, 24 DE mRNAs related with floral transition were predicted, and these involved the following: three interactions between the DE lncRNAs and DE mRNAs of photoperiod pathway with two mRNAs (COP1, PaF106G0400018289.01 and CO3, MXLOC_025744) and three lncRNAs (CCLR, LTCONS_00031803, COCLR1, LTCONS_00046726 and COCLR2, LTCONS_00046731); one interactions between DE miRNAs and DE mRNAs with one mRNA, encoding trehalose-6-phosphate synthase (PsTPS1, PaF106G0100001132.01), and one miRNA (miRNA167h). Combined with the expression profiles and Tre6P levels, the functions of PsTPPF and PsTPS1 in Tre6P regulation were considered to be associated with flowering time. A new ceRNAs network correlated with late flowering was constructed, and it consisted of one mRNA (PsTPS1), one lncRNA (TCLR, LTCONS_00034157), and one miRNA (miR167h). This study provided insight into the molecular regulatory mechanism of late flowering in Prunus sibirica.